Sawtooth induced q-profile evolution at ASDEX Upgrade. (26th March 2019) - Fischer, R.; Bock, A.; Burckhart, A.; Ford, O.P.; Giannone, L.; Igochine, V.; Weiland, M.; Willensdorfer, M.
Abstract: The sawtooth induced q -profile evolution was modelled at ASDEX Upgrade and validated with imaging motional Stark effect (IMSE) measurements. The equilibrium current distribution was estimated by the coupling of a Grad–Shafranov solver and the current diffusion equation. At ASDEX Upgrade an extensive diagnostic suite allows for a reliable modelling of the current density profile and its temporal evolution as long as neo-classical current diffusion can be assumed. The sawtooth-induced central q change, , was estimated from equilibrium reconstruction between the sawtooth events without using IMSE measurements. The sawtooth-induced current relaxation is modelled with two different reconnection models, a Kadomtsev full reconnection and a newly developed fully stochastic flat-current model. Both models result in about the same sawtooth-induced 0.10–0.12 but with a small difference in the absolute q 0 values. The sawtooth-induced evolution of the forward modelled MSE angles agrees well with the IMSE measurements. This confirms the assumption of neo-classical current diffusion between the sawtooth events. A sensitivity study reveals two major ingredients for a reliable interpretation of MSE measurements. Firstly, the sawtooth-induced redistribution of fast ions has to be taken into account for a reliable estimation of the Shafranov shift. The fast-ion redistribution is modelled with a particle-conserving homogeneous fast-ion pressure profile in the plasma core and a subsequent recovery time of 50 ms. Secondly, a reliable estimation of the electric field is necessary for a credible interpretation of the MSE angles.